Linking Cash Flow Management to Shareholder Value: Insights from SMEs in Delhi NCR - Keswani, Tanuj (Digital Repository of Theses - SSBM Geneva, 2025)
The dissertation explores the relationship between cash flow management practices and their impact on financial metrics and shareholder value across various organizational sizes, focusing on small and medium-sized enterprises (SMEs). Through a series of analyses, this study investigates how uniformly cash flow management practices are applied across different company sizes, how these practices influence financial metrics such as profit margins and cash reserves, and their ultimate impact on shareholder value. A comprehensive dataset from a range of SMEs provided a robust foundation for a series of chi-square tests, correlation matrices, and regression analyses to understand the frequency and effectiveness of cash flow management practices. The findings revealed a high level of uniformity in adopting these practices across companies of all sizes, suggesting that financial management techniques are standardized within the industry, possibly due to regulatory influences and universally recognized best practices. Further, the study examined the effect of these practices on key financial metrics. It was observed that proactive cash flow management, including effective budgeting and credit management, was positively received by organizations, yet challenges in achieving forecasting accuracy and financial stability were evident. These challenges highlight potential areas for improvement in the tools and methods used for financial management within SMEs. Additionally, the research delved into how these cash flow management practices impact shareholder value. It found a positive correlation between consistent earnings and the ability to attract investors, emphasizing the role of effective cash flow management in enhancing shareholder value. External factors such as market conditions, regulatory costs, and competitive pressures were also analyzed to understand their impact on cash flow management. The findings suggest that while these factors significantly affect financial strategies, the degree of impact varies widely across companies. This dissertation contributes to the academic literature by providing empirical evidence on the standardized application of cash flow management practices across SMEs and their impact on financial performance and shareholder value. Recommendations for future research include exploring the role of advanced technological tools in enhancing the accuracy of financial forecasting and the need for tailored financial strategies that address the unique challenges businesses face in varying market conditions.